Beyond the veil of stars - Reed, Robert. 1956- (TOR, 1994)
A change in the universe creates time warps through which humans can travel to other worlds. In the process they are adapted for the new environment, say by taking on animal bodies, or acquiring powers of telepathy. By the author of The Hormone Jungle.